What do we know about business process management training? Current status of related research and a way forward. Issue 2 (3rd April 2018) - Thennakoon, Dharshani; Bandara, Wasana; French, Erica; Mathiesen, Paul
Abstract : Purpose: There is wide acknowledgment that training people from all levels of an organization in process management activities and "process thinking" is a major contributor to the success or failure, and sustainability of business process management (BPM). BPM training is provided in almost all BPM initiatives and involves the investment of valuable financial, human, information and other resources. However, little research has focused on this area. As a result, there is a lack of guidance for organizations in conducting value adding BPM training. The purpose of this paper is to consolidate the current published knowledge on BPM training in the form of a descriptive literature review to paint a picture of the existing work, identify gaps and propose a program of work for the future. Design/methodology/approach: A structured descriptive literature review was conducted to understand the current status of literature on training in the domain of BPM. Of an initial search of 90 publications, 64 publications, published between 1994 and 2015, were filtered and reviewed based on their relevance to answer the research question: What has BPM literature mentioned of training people for BPM? This study proposes a research agenda based on this. A grounded theory coding approach was employed, where NVivo 10 was used as a tool to support the analysis. Findings: A total of 234 codes (representing emerging themes) were inductively identified from the data. These codes were further analyzed, resulting in eight core themes pertaining to training in the BPM context. Research limitations/implications: The paper presents a vivid descriptive overview of the current status of research in BPM training identifying gaps in the literature and presents a research agenda which supports a call for action. Originality/value: The paper is the first known of its kind to compile the status of literature focused on BPM training and recommend a research agenda based on such.